2019
DOI: 10.31235/osf.io/fsne7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lecturer’s Language Style and Students’ Academic Self Efficacy in Higher Education of Indonesia

Abstract: This research is aimed at finding out the influence of lecturers’ language style on students’ academic self-efficacy in higher education in Indonesia. This research is conducted to describe the correlation between lecturers’ language style and students’ academic. As one of the aspects of forming academic self-efficacy, language style has an important role because someone who can get information verbally about his ability in mastering certain duty tends to do more efforts. In addition, it mak… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Corpus-based analyses on academic writings also indicate that lexical and stylistic characteristics, such as vocabulary use, specific terminology, and stylistic features, are distinct between economics and other fields (Goldschmidt & Szmrecsanyi, 2007). A plethora of research has indicated a strong correlation between language style and gender (Pânişoară, Sandu, Pânişoară, & Duţă, 2015), academic performance (Robinson et al 2013, Gunawan, Mayasari, & Masruddin, 2019, leadership personality traits (Pennebaker & King, 1999, Vries, Bakker-Pieper, & Oostenveld, 2009, Solaja, Idowu, & James, 2016, social hierarchies (Irvine, 1985, Pennebaker, 2011, interpersonal skills (Vries, Bakker-Pieper, Siberg, Gameren, & Vlug, 2009), narrative effects , and romantic relationships . However, it is not known what factors contribute to the differences in communication style used by scholars of different academic disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Corpus-based analyses on academic writings also indicate that lexical and stylistic characteristics, such as vocabulary use, specific terminology, and stylistic features, are distinct between economics and other fields (Goldschmidt & Szmrecsanyi, 2007). A plethora of research has indicated a strong correlation between language style and gender (Pânişoară, Sandu, Pânişoară, & Duţă, 2015), academic performance (Robinson et al 2013, Gunawan, Mayasari, & Masruddin, 2019, leadership personality traits (Pennebaker & King, 1999, Vries, Bakker-Pieper, & Oostenveld, 2009, Solaja, Idowu, & James, 2016, social hierarchies (Irvine, 1985, Pennebaker, 2011, interpersonal skills (Vries, Bakker-Pieper, Siberg, Gameren, & Vlug, 2009), narrative effects , and romantic relationships . However, it is not known what factors contribute to the differences in communication style used by scholars of different academic disciplines.…”
Section: Introductionmentioning
confidence: 99%